2010
DOI: 10.1021/ma101827u
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring PMMA Elimination by Reactive Ion Etching from a Lamellar PS-b-PMMA Thin Film by ex Situ TEM Methods

Abstract: Block copolymer thin films require selective elimination of one of their constituent blocks to access their potential as lithographic nanopatterns. This paper demonstrates an on-substrate TEM-based approach for establishing the removal of poly(methyl methyacrylate) from vertically oriented lamellar polystyrene-block-poly(methyl methacrylate) (PS-b-PMMA) thin films and subsequent transfer to the underlying silicon by reactive ion etching. The ex situ microscopy technique presents an insight into the removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…However, it requires brush layer on top of the silicon substrate to form the well aligned structure which is time consuming method [21]. Etching of PS-PMMA suffers from rounding of the pattern, which can cause problems for device fabrication [22]. Another high chi system, PS-PDMS showed promising patterns but it also required the brush layer as well as poor pattern transferability [23, 24].…”
Section: Block Copolymers In Nanoscience and Nanotechnologymentioning
confidence: 99%
“…However, it requires brush layer on top of the silicon substrate to form the well aligned structure which is time consuming method [21]. Etching of PS-PMMA suffers from rounding of the pattern, which can cause problems for device fabrication [22]. Another high chi system, PS-PDMS showed promising patterns but it also required the brush layer as well as poor pattern transferability [23, 24].…”
Section: Block Copolymers In Nanoscience and Nanotechnologymentioning
confidence: 99%
“…However, the minimum feature size that can be achieved by orientation of PS-b-PMMA is approximately 13 nm since the χ parameter for PS-b-PMMA is only 0.037 at 150°C, the temperature near which the system is typically annealed [9]. Furthermore, the etch selectivity between PS and PMMA is not high [10].…”
Section: Introductionmentioning
confidence: 99%
“…In general, nanoparticle self-assembly development has been limited because the synthesis of size mono-dispersed particles is challenging for all but a few systems and thin films of these tend to lack thermal and mechanical robustness. Compared to other techniques, BCP systems offer a combination of experimental advantages; thin films can be formed from simple solutions, the resultant films are robust, the feature size is highly controllable using polymer engineering and the films are readily processed (e.g., in pattern transfer where the polymer pattern is transferred to the surface by selective etch processes (Borah et al, 2011 andFarrell et al, 2010). Authors have demonstrated many applications for microphase separated BCP thin films.…”
Section: The Need For Low Defect Concentrations In Self-assembled Sysmentioning
confidence: 99%